PENGARUH BUDAYA ORGANISASI, WORK DISCIPLINE TERHADAP EMPLOYEE PERFORMANCE PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KOTA PADANGSIDIMPUAN - Yusditara, Wisnu; harahap, Nirmala Haty; Nurdelila (Jurnal KAFEBIS, 2023)
This study aims to determine the influence of Organizational Culture and Work Discipline on Employee Performance at the Investment and One-Stop Integrated Services Department in Padangsidimpuan City. The analysis method used is multiple linear regression processed with SPSS version 24. The results of the research show that Organizational Culture and Work Discipline have a significant effect on Employee Performance with a significance value of each variable being 0.045 and 0.000, respectively. The regression coefficient for Organizational Culture is 0.567 and for Work Discipline is 0.334, indicating that Organizational Culture has a greater influence than Work Discipline in improving Employee Performance. In addition, the F test gives an F-count value of 65.245 with a significance of 0.000, indicating that Organizational Culture and Work Discipline simultaneously influence Employee Performance. Further analysis shows that 81.8% of the variability of Employee Performance can be explained by these two variables, while the rest is influenced by other factors not discussed in this research. These findings reinforce the hypothesis that Organizational Culture and Work Discipline significantly affect Employee Performance.